Análise dinâmica não linear de colunas de perfuração - Martins, Leandro Augusto (2023)
This doctoral thesis is dedicated to the numerical and experimental investigation of drill strings used in oil and gas exploration. A nonlinear numerical/computational model was developed in finite elements from the inclusion of non-linear terms in a traditional beam model. This alteration is carried out to enable the correct coupling between torsion/flexion, allowing the correct representation of complex effects arising from the non-linear dynamics of the column in operation. In order to allow the investigation of these phenomena in an experimental way, a test rig was designed, built, and instrumented. Its components, layout, and purpose are presented and justified in detail. The rig was structured aiming robustness, allowing different situations and scenarios, and admitting that axial, torsional, and lateral vibrations could be investigated. The numerical simulations showed the differences between the traditional linear model and the proposed one, counting on its validation. The model was then incorporated into a reference configuration, which was investigated dynamically, being able to reproduce stick-slip, bit-bounce and helical buckling. The experimental investigations using the test rig present at the University of Aberdeen brought valuable results, allowing the elucidation of several effects, how they occur, and their impact on the dynamics of the system. Additionally, through these, the coupling between the different types of vibrations can be observed, qualitatively agreeing with the numerical simulations. Based on the discussions held as well as the results obtained, the main contributions are presented at institutional and general levels